Sumangano Ompu Masyarakat Cia-cia Laporo - La Pande Jurumai (Arsitektur Universitas Muhammadiyah Kendari, 2022)
Ciacia laporo is an indigenous people who have inhabited the mainland of Buton since the people settled in Lipumangau and Bugi Lama. The people who live in the interior leave a history of living and cultural heritage. The most important trace of living and cultural heritage is the concept of sumangano ompu, which is the way of life for the people of Ciacia Laporo wherever they are. This study uses inductive qualitative methods such as observation and interviews with a phenomenological model, which has led researchers to go into the field without a solid theory to explore in the field. To support this research, several means of collecting field data are available, such as: area maps, imaging equipment, use of sketches and cameras. From the results of the analysis, it can be seen that these topics have given rise to the concept, meaning and theory of the Sumangano Ompu concept of the Cia-cia Laporo tribe. The spaces are formed from the habit of moving farmers and the habit of moving houses to new villages. The habit of shifting cultivation means avoiding evil, seeking a better life without destroying nature, the meaning of moving a house without using new materials is to respect and appreciate the ompu heritage house in the use of nature as a food source, as well as in the use of space to maintain the culture inherited from the ancestors. Keyword: Concept, Sumangano Ompu, Cia-cia Laporo